Global partnership in poverty reduction: Contract farming and regional cooperation - Sununtar Setboonsarng (Asian Development Bank Institute (ADBI), 2008)
With globalization, market liberalization, and the rapid development of rural infrastructure, new market opportunities for high-value crops and livestock production are expanding in both developed and developing countries. This has translated into increased use of contract farming to establish market linkages for the poor in developing countries. In poor areas where smallholder subsistence production is the norm and where infrastructure and institutions to facilitate market exchange are not well established, contract farming is providing farmers with the assured sale of their crops and agro-business firms with a steady supply of agricultural output required by the market. In many instances, agro-business firms provide additional provisions, including technical support, improved farm inputs, credit, product accreditation, and assistance in the formulation of farmers' groups. Consequently, poor farmers are able to transform from traditional cultivation and management practices to market-oriented commercial production, resulting in employment generation, income growth, and greater security. This paper reviews the pros and cons of contract farming from the point of view of different stakeholders, e.g., firms, farmers, government, and donors. In particular, this work examines contract farming in the Lao PDR and Cambodia and points to contract farming of organic crops as a promising option for poor farmers as the practice is consistent with traditional practices while associated with lower health and environmental risks. While the development of market linkages for farmers is traditionally viewed as a public sector responsibility, the establishment of necessary agro-services for a large number of small, unorganized farmers requires a tremendous amount of public sector resources. Given the limited availability of government and donor resources, private sector endeavors that serve to generate pro-poor growth may be the key to poverty alleviation.
Keywords: O43; Q17; Q56; 330; Vertragsanbau; Globalisierung; Internationale Wirtschaftsbeziehungen; Armut; Landwirtschaftliche Entwicklung; Laos; Kambodscha; Asien